Analisis Performa 5G NSA ISP Telkomsel di Sumatera Barat - Muhammad Rafi; Muhammad Putra Pamungkas; Sri Yusnita (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Telkomsel has introduced 5G technology in Padang City, evaluated through drive tests using G-Nettrack Pro software to measure Reference Signal Received Power (RSRP) and Signal to Interference plus Noise Ratio (SINR). The tests revealed RSRP values ranging from -44 dBm to -100 dBm and SINR values between -12 dB and 26 dB. While high RSRP does not always guarantee high throughput, higher SINR consistently improves throughput, with the highest throughput reaching 153,053 kbps at SINR levels between 10 and 30 dB. Modulation and Carrier Aggregation (CA) also play a significant role, with 64-QAM modulation combined with CA achieving throughput up to 31,500 kbps, compared to 6,300 kbps without CA. Although CA bandwidth decreased from 100 MHz to 50 MHz, throughput remains higher compared to 20 MHz bandwidth without CA. CA proves highly effective in enhancing throughput through larger bandwidth and more efficient modulation. Additional factors such as handover, interference, and physical and weather conditions also impact network performance. Overall, Telkomsel’s 5G network in Padang City meets the company’s Key Performance Indicators (KPI), despite some areas with suboptimal signal quality.